Unveiling risk factors and sandfly ecology in cutaneous leishmaniasis-endemic areas of the Asir Region, Saudi Arabia - Yasser Alraey; Abdulaziz Alshahrani; Thunan Saad M. Alshahrani; Nasser Hassan Awdah Al Draim; Abdulqader A. Sumayli; Abdullah M. Mana; Abdulrahman Abdullah Alqahtani; Mohammed Saad AlAbdullah; Abdulmajeed M. Mjrashi; Saeed j Alqhtani; Waleed S. Al Salem (Journal of Infection and Public Health)
Background: Cutaneous leishmaniasis (CL) remains a significant public health challenge in the Asir region of southwest Saudi Arabia. This study aimed to identify risk factors associated with CL transmission through a case-control questionnaire and to investigate the local sandfly population as potential vectors. Method: From June to December 2022, sandflies were collected using paper traps from four CL-endemic locations: Khamis Mushait, Belhamr, Mahayel, and Rijal Almaa. Collected specimens were taxonomically identified. Concurrently, between 2022 and 2023, a validated questionnaire was administered to confirmed CL cases and matched controls without prior CL history. The questionnaire assessed demographic data, lesion characteristics, medical history, housing conditions, animal exposure, and use of protective measures. Interviews were conducted in Arabic and English, with translation support as needed. Results: A total of 713 sandflies were captured, including 453 males and 260 females. Khamis Mushait showed the highest vector abundance. Two sandfly genera, Phlebotomus and Sergentomyia, were identified. Among six Phlebotomus species, Ph. bergeroti and Ph. sergenti were the most prevalent. Questionnaire analysis revealed that men and married individuals were more frequently affected. Risk factors included outdoor activity, poor housing infrastructure, and proximity to livestock and gardens. In contrast, waste areas showed no significant association, and the use of insecticides and public health awareness were correlated with reduced infection risk. Conclusions: This study highlights key environmental, entomological, and behavioral factors influencing the Asir region's cutaneous leishmaniasis (CL) transmission. Ph. bergeroti and Ph. sergenti were the most abundant species, with Ph. bergeroti showing potential as a permissive vector, warranting further investigation. The findings suggest the possibility of a zoonotic transmission cycle in an area traditionally considered non-zoonotic for Leishmania tropica, emphasizing the need for integrated control and public health strategies.